Characteristic Study of Film Thickness on Countercurrent of Water-Air Flow in Hot-Leg Simulator of L/D = 25 by using Parallel-Wire Methods - Radhi Ariawan (University of Muhammadiyah Malang, 2017)
In water-air counter current flow, relative movement between water and air occurred. The results of this movement interfacial instability occurred in the flow, causing the liquid film moves up and down. In this study, film thickness characteristics of water-air counter current flow in L/D=25 hot-leg simulator are identified. Film thickness measurement was carried out using parallel-wire sensor consists of parallel wires installed through the pipe’s cross sectional area with spacing of 5 mm. sensor has wire diameter of 0,51 mm made from copper coated in silver. This experimental study was carried out with water superficial velocity (JL) variation of JL=0,003 m/s, JL=0,032 m/s, and JL=0,065 m/s. From the film thickness measurement, film thickness characteristics of water-air counter current flow are identified based on the flow pattern and the position of onset of flooding. JL variation affects the occurring time of flow pattern change, hydraulic jump, and onset of flooding. Hydraulic jump and onset of flooding position occurred further from the bend as the JL increased. Onset of flooding occurrence time is faster as the JL bigger.